1997
DOI: 10.1111/j.1540-8191.1997.tb00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Reconstruction and Mitral Valve Replacement for Ischemic Mitral Insufficiency

Abstract: We conclude that patients with highly impaired left ventricular function and ischemic mitral insufficiency are at too great a risk for either valve reconstruction or replacement. Cardiac transplantation should be considered for this patient group. However, patients with ischemic mitral insufficiency and moderately impaired left ventricular function can undergo valve reconstruction or replacement with an acceptable prognosis. The goal of mitral valve reconstruction should be reducing mitral valve insufficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 17 publications
4
70
2
Order By: Relevance
“…20) Many techniques to reduce the incidence of recurrent MR have been attempted, including annuloplasty using different ring (asymmetric, rigid, flexible, complete, or partial) and procedures for papillary muscles or tethered leaflets. 21,22) However, randomized data on the results of these repair techniques are lacking, and the results of observational studies are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…20) Many techniques to reduce the incidence of recurrent MR have been attempted, including annuloplasty using different ring (asymmetric, rigid, flexible, complete, or partial) and procedures for papillary muscles or tethered leaflets. 21,22) However, randomized data on the results of these repair techniques are lacking, and the results of observational studies are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…32,41 However, in addition to advanced age, these patients may have several contraindications to transplantation; moreover, the scarce supply of organs makes this therapeutic option particularly limited.…”
Section: Surgical Intervention For Imrmentioning
confidence: 99%
“…5 It is also important to consider that the addition of mitral valve surgery to revascularization adds to the operative risk of revascularization alone. 9,19,[31][32][33] The morbidity and mortality associated with combined mitral valve replacement and revascularization are high, and long-term survival after this combination is quite poor. 2,[7][8][9] Because of this high morbidity and mortality, some authors have suggested revascularization alone for treatment of IMR.…”
Section: Surgical Intervention For Imrmentioning
confidence: 99%
“…1 Ring annuloplasty, the standard surgical treatment for CIMR, has frustratingly variable results and can be associated with residual or recurrent mitral regurgitation (MR), which is found in upwards of 30% of patients [2][3][4] and is associated with a poor prognosis. 5 Subvalvular adjuncts to ring annuloplasty for CIMR have been proposed, 6,7 but quantitative 3-dimensional analysis of the perturbations of the valvular-ventricular complex associated with CIMR is required for rational design of improved repair methods. The purpose of this study was to gain mechanistic insight into the pathogenesis of CIMR by examining the distortions of the mitral valvular-ventricular apparatus in an ovine model of chronic infarction.…”
mentioning
confidence: 99%